Strategic Retail Management - Zentes, Joachim; Morschett, Dirk; Schramm-Klein, Hanna (Springer, 2017)
The economic importance of retailing is constantly increasing, as can be seen from the development of many countries across Europe, America and Asia. In highly developed countries, retailers are taking an increased leadership role in every distribution channel. Expansion strategies, retail branding strategies, innovative solutions for supply chain management and many other developments all reflect this trend. Transformation countries such as those in Central and Eastern Europe and emerging countries such as China or Brazil are also seeing fundamental changes in retailing structures, which may lead to comparable developments. Internationalisation has also led to profound changes. Formerly local or national retailers are increasingly developing into global players with worldwide operations.
Text and International Cases